A comparative study on the clinical features of COVID‐19 with non‐SARS‐CoV‐2 respiratory viral infections. Issue 3 (29th September 2020) - Tan, Jing Yuan; Sim, Xiang Ying Jean; Wee, Liang En; Chua, Ying‐Ying; Cherng, Benjamin Pei Zhi; Ng, Ian Matthias; Conceicao, Edwin Philip; Wong, Tzu‐Jung; Yang, Yong; Aung, May Kyawt; Ling, Moi Lin; Venkatachalam, Indumathi
Abstract: During this coronavirus disease 2019 (COVID‐19) pandemic, physicians have the important task of risk stratifying patients who present with acute respiratory illnesses. Clinical presentation of COVID‐19, however, can be difficult to distinguish from other respiratory viral infections. Thus, identifying clinical features that are strongly associated with COVID‐19 in comparison to other respiratory viruses can aid risk stratification and testing prioritization especially in situations where resources for virological testing and resources for isolation facilities are limited. In our retrospective cohort study comparing the clinical presentation of COVID‐19 and other respiratory viral infections, we found that anosmia and dysgeusia were symptoms independently associated with COVID‐19 and can be important differentiating symptoms in patients presenting with acute respiratory illness. On the other hand, laboratory abnormalities and radiological findings were not statistically different between the two groups. In comparing outcomes, patients with COVID‐19 were more likely to need high dependency or intensive care unit care and had a longer median length of stay. With our findings, we emphasize that epidemiological risk factors and clinical symptoms are more useful than laboratory and radiological abnormalities in differentiating COVID‐19 from other respiratory viral infections. Highlights: Ansomia and dysgeusia are important differentiating symptoms for coronavirus disease 2019 (COVID‐19) from other respiratory viruses. Epidemiology history and clinical symptoms are important in the risk stratification of patients who present with acute respiratory illness. Initial laboratory and radiological findings are less important in risk stratification.